Relationship Between Work Motivation And Nurse Performance At Rejoso Puskesmas, Nganjuk Regency - Wahyudi (Journal of Hospital Management and Services, 2022)
Performance is the result of work achieved by a person or group of people in an organization according to their authority and responsibility. Good performance can be achieved by increasing work motivation. The higher a person's work motivation, the higher the resulting performance. This study aims to determine the relationship between work motivation and the performance of nurses at the Rejoso Public Health Center, Nganjuk Regency. This research design is quantitative with a case study approach. Data collection using techniques by distributing questionnaires to respondents. This research was conducted at the Rejoso Health Center, Nganjuk Regency in March 2022. This study took the total population of nurses at the Rejoso Health Center, Nganjuk Regency. The samples obtained were 29 nurses who met the inclusion and exclusion criteria. The research instrument is a questionnaire to measure work motivation and a questionnaire to measure the performance of nurses. Analysis using data analysis techniques Spearman rank correlation can also be calculated through the SPSS 16.0 application for windows. The results of this study indicate that N or the number of research data is 29, then the value of sig. (2-tailed) is 0.002, as the basis for the decision maker above, it can be concluded that there is a significant relationship between work motivation and performance. Furthermore, from the output above, it is known that the correlation coefficient is 0.544, so this value indicates a high relationship between work motivation and performance at the Rejoso Health Center, Nganjuk Regency. nurses are more motivated to perform better.